Preparation process and hydration mechanisms of low-clinker cementitious materials by using oil shale ash slag - Zhiyuan Chen; Siqi Zhang; Wen Ni; Yang Yu; Xin Li (Case Studies in Construction Materials)
Oil shale ash slag (OSAS), a byproduct of retorting and combustion, poses environmental risks when disposed via conventional stockpiling or landfilling. Although utilized in construction materials, its complex composition limits technological maturity. This study elucidates hydration mechanisms in the OSAS-clinker-desulfurized gypsum ternary system to overcome technological bottlenecks in high-value OSAS utilization, providing theoretical foundations for low-clinker cementitious materials design. Using Beita OSAS, multi-scale characterization (XRD, TG-DSC, FT-IR, SEM-EDS) and mortar tests identified the optimal mix A7: 25 % clinker + 65 % OSAS + 10 % desulfurized gypsum, achieving compressive strengths of 28.05 MPa at 3d and 61.99 MPa at 28d with 0.35 water-to-binder ratio and 1.0 % superplasticizer. The system exhibited a normal consistency water requirement of 194 g, with initial and final setting times of 125 min and 175 min respectively, while its soundness was validated. Hydration analysis reveals that clinker hydration provides initial C-(A)-S-H gel, Ca(OH)2, and Ca2 + , while desulfurized gypsum supplies SO42-, continuously activating reactive Si-Al phases in OSAS to form C-A-S-H gel and AFt. AFt fills macropores and C-A-S-H gel seals nanopores, collectively enhancing system densification and strength. This clarifies the activation pathway of OSAS by clinker and desulfurized gypsum, resolving the low reactivity issue in conventional OSAS cement. The system reduces clinker consumption to 25 %, transforming OSAS from environmental liability to low-carbon construction resource.